Optimization of Post-Endodontic Restoration: Strategies for Handling Deep Subgingival Margin through DME and Crown Lengthening - Putra, Hariansyah Buana; Asrianti, Dini (Odonto : Dental Journal, 2025)
Background: Post-endodontic restoration with deep subgingival marginsbeyond the cementoenamel junction (CEJ) is a challenge in itself. Thiscondition can cause difficulties in insulation with rubber dams, molding, andrestoration cementing. The subgingival margin is also at risk of triggeringgingival inflammation and invasion of biological width (BW) due to its proximityto the alveolar bone. Surgical crown lengthening (CL) is often recommended torestore the ideal distance of the BW, but the procedure is invasive. As a moreconservative alternative, Deep Margin Elevation (DME) allows elevation of thesubgingival to supragingiva margin to improve the integrity of the restorationwithout invading the BW.Case report: The first case on the interproximal teeth 24 and 25 (BoneSounding: 1mm) was performed CL by the Periodontics department prior tocrown preparation, after previously undergoing endodontic and post fibertreatment in the Dental Conservation department. The second case was in 36previously treated teeth (Bone Sounding: 2mm) with deep subgingival margins,DME was performed using a high-filler composite resin prior to onlayrestoration. Both procedures were carried out at RSKGM FKG UI.Conclusion: Proper indication for CL and DME at the deep subgingival margincan improve the optimization of periodontal health and the integrity of postendodontic restoration.